Relationship between depressive symptoms and internet usage time among adolescents: Results from a nationwide survey. (July 2022) - Wu, Hua; Ji, Jia-Mei; Qian, Yan; Jin, Xiao-Hong; Yu, Hai-Rong; Liu, Xiao-Man; Du, Lin; Fu, Xue-Lei; Chen, Hong-Lin
Highlights: A large sample of Chinese adolescents are involved. Adolescents with more internet usage time showed elevated odds of experiencing depressive symptoms. Supervising and managing online time can contribute to the prevention and intervention of adolescent depression symptoms. Abstract: Adolescent depression is becoming a public health problem. In this study the association between depressive symptoms and internet usage time in adolescents was examined, with data collected from the China Education Tracking Survey (CEPS). The survey is publicly available and carried out nationwide. A logistic regression analysis was conducted with odds ratios (OR) and 95% confidence intervals (CI), the subgroup analysis examined the relationships between internet usage time and depressive symptoms. A total of 10, 705 adolescents were involved, where 46.4% of them are caught by the internet for more than two hours per day. Adolescents keeping on the internet for 6–8 h per day were reported to have higher odds of depressive symptoms than adolescents who were free from it with the confounders of individual, family, and school adjusted, which were observed among groups with a medium family economic status without living with their father and with a sleep time less than nine hours. The results revealed that adolescents spending more time online had a higher risk of experiencing depression symptoms. This study suggested that it is helpful for mental health professionals to evaluate and develop prevention interventions for depressive symptoms in adolescents promptly through monitoring and managing online time.